EXPERIMENTAL RESEARCH OF A SMALL-SIZED COMPRESSOR UNIT FOR ABNORMAL OIL AND GAS PRODUCTION CONDITIONS - Sazonov, Yuri; Mokhov, Mikhail; Pyatibratov, Petr; Frankov, Mikhail; Voronova, Victoria; Gryaznova, Inna (Journal of Applied Engineering Science, 2020)
At the late stage of field development, the application of booster compressor units often becomes an urgent problem. At the same time, this problem remains completely unsolved. Reliable hydraulic machines are required for pumping gas-liquid mixtures with a high content of mechanical impurities. Within the framework of exploratory scientific researches, the practical opportunities to use a group of dynamic type hydraulic machines were assessed. In this respect, the greatest interest from a scientific and practical point of view is small-sized high-speed machinery with the possibility of creating universal multistage pumps and compressors. Labyrinth pumps and compressors which work more reliably at an increased concentration of mechanical impurities in the flow of the pumped medium are considered. The new equipment should be characterized by manufacturability, low price and low maintenance costs. As part of the research, new technical solutions are being developed and patented to create a small-sized compressor unit for a wide range of oil and gas production tasks in abnormal operating conditions. The technical problem targeted by the research is to increase the efficiency of the dynamic machine operation in the compressor and multiphase pump modes when pumping gases and gas-liquid mixtures in abnormal operating conditions. New developments can also be focused on improving the efficiency of production and deep processing of raw hydrocarbons, including as it relates to the Arctic environment. It is reasonable to focus further research on optimizing the use of different rotor designs with new materials and new design methods, including additive technologies. The direction of research aimed at increasing the rotor speed is seen as very promising. There is an opportunity to create compact and powerful compressor machinery and pumping equipment.
Keywords: oil production; oil; gas; compressor; multi-phase pump